Organizational Conditions That Impact the Implementation of Effective Team-Based Models for the Treatment of Diabetes for Low Income Patients—A Scoping Review - Levis-Peralta, Maria; González, Maria del Rosario; Stalmeijer, Renée; Dolmans, Diana; de Nooijer, Jascha (Frontiers in Endocrinology, 2020)
Background Team-based care models (TBC) have demonstrated effectiveness to improve health outcomes for vulnerable diabetes patients but have proven difficult to implement in low income settings. Organizational conditions have been identified as influential on the implementation of TBC. This scoping review aims to answer the question: What is known from the scientific literature about how organizational conditions enable or inhibit TBC for diabetic patients in primary care settings, particularly settings that serve low-income patients? Methods A scoping review study design was selected to identify key concepts and research gaps in the literature related to the impact of organizational conditions on TBC. Twenty-six articles were finally selected and included in this review. This scoping review was carried out following a directed content analysis approach. Results While it is assumed that trained health professionals from diverse disciplines working in a common setting will sort it out and work as a team, co-location and health professions education alone do not improve patient outcomes for diabetic patients. Health system, organization and/or team level factors affect the way in which members of a care team, including patients and caregivers, collaborate to improve health outcomes. These organizational factors are cited throughout the literature as important to TBC, however, research on the organizational conditions that enable and inhibit TBC for diabetic patients is extremely limited. Dispersed organizational factors are cited throughout the literature, but only one study specifically assesses the effect of organizational factors on TBC. Thematic analysis was used to categorize organizational factors in the literature about TBC and diabetes and a framework for analysis and definitions for key terms is presented. Conclusions The review identified significant gaps in the literature relating to the study of organizational conditions that enable or inhibit TBC for low-income patients with diabetes. Efforts need to be carried out to establish unifying terminology and frameworks across the field to help explain the relationship between organizational conditions and TBC for diabetes. Few studies include information on patient outcomes, and fewer include information on low income settings. Further research is necessary on the impact of organizational conditions on TBC and diabetic patient outcomes.